Familial Cerebellar Ataxia and Amyotrophic Lateral Sclerosis/Frontotemporal Dementia with and Repeat Expansions: An 18-Year Study - Rosenbohm, Angela; Pott, Hendrik; Thomsen, Mirja; Rafehi, Haloom; Kaya, Sabine; Szymczak, Silke; Volk, Alexander E.; Mueller, Kathrin; Silveira, Isabel; Weishaupt, Jochen H.; Tönnies, Holger; Seibler, Philip; et al. (Movement disorders, 2022)
Background Coding and noncoding repeat expansions are an important cause of neurodegenerative diseases. Objective This study determined the clinical and genetic features of a large German family that has been followed for almost 2 decades with an autosomal dominantly inherited spinocerebellar ataxia (SCA) and independent co-occurrence of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). Methods We carried out clinical examinations and telephone interviews, reviewed medical records, and performed magnetic resonance imaging and positron emission tomography scans of all available family members. Comprehensive genetic investigations included linkage analysis, short-read genome sequencing, long-read sequencing, repeat-primed polymerase chain reaction, and Southern blotting. Results The family comprises 118 members across seven generations, 30 of whom were definitely and five possibly affected. In this family, two different pathogenic mutations were found, a heterozygous repeat expansion in C9ORF72 in four patients with ALS/FTD and a heterozygous repeat expansion in DAB1 in at least nine patients with SCA, leading to a diagnosis of DAB1-related ataxia (ATX-DAB1; SCA37). One patient was affected by ALS and SCA and carried both repeat expansions. The repeat in DAB1 had the same configuration but was larger than those previously described ([ATTTT]≈75[ATTTC]≈40-100[ATTTT]≈415). Clinical features in patients with SCA included spinocerebellar symptoms, sometimes accompanied by additional ophthalmoplegia, vertical nystagmus, tremor, sensory deficits, and dystonia. After several decades, some of these patients suffered from cognitive decline and one from additional nonprogressive lower motor neuron affection. Conclusion We demonstrate genetic and clinical findings during an 18-year period in a unique family carrying two different pathogenic repeat expansions, providing novel insights into their genotypic and phenotypic spectrums. © 2022 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society.